A comprehensive performance evaluation of phase change materials for cold energy storage systems - Altuntas, Merve; Erdemir, Dogan; Unalan, Sebahattin (ELSEVIER SCIENCE SA, 2025)
The increasing need for cooling, particularly air conditioning, is driving a significant rise in building energy consumption. This surge in demand often leads to peak loads, straining power grids and increasing costs. Cold thermal energy storage systems, especially those utilizing phase change materials, offer a promising solution to mitigate these challenges. This study presents a comprehensive investigation and performance assessment of various phase change materials for efficient cold energy storage applications. Phase change materials are considered encapsulated, one of the most common techniques in cold thermal energy storage applications. The primary objective is to develop a comprehensive methodology for the system's design and then identify the most suitable phase change material for better system performance. The research also studies the impact of storage tank porosity, diameter-to-height ratio, and pressure drop on system performance for a 1 MWh cooling capacity. The performance assessment considers all essential power drivers of the practical systems. The findings reveal that water/ice is the most efficient phase change material, requiring the smallest mass and exhibiting the highest overall system COP values by lowering the heat transfer fluid pump and chiller powers. Specifically, it has been determined that water/ice is the most efficient phase change material, requiring the smallest mass quantity of 10.4 tons and demonstrating overall coefficient of performance values ranging from approximately 3.98 to 4.37 for different heat transfer fluid options. This research contributes to the development of sustainable and costeffective cooling solutions, addressing the growing energy demands of the building sector and promoting a more resilient and efficient energy infrastructure.
Keywords: Cold thermal energy storage; Phase change material; PCM; Cooling load; Heat storage; Packed-bed thermal energy storage tank; ORGANIC OXYGEN COMPOUNDS; THERMODYNAMIC PROPERTIES; THERMAL PERFORMANCE; HEAT-CAPACITY; OPTIMIZATION; TETRADECANE; Construction & Building Technology; Energy & Fuels; Engineering